Rethinking Performance-based Budgeting: The Case of the Russian Healthcare System - Dokalskaya, Irina; Pauluzzo, Rubens (Mecosan - Management ed Economia Sanitaria - Open Access, 2024)
Aiming to enhance efficiency, performance, and accountability in the management of the public sector, performance-based budgeting (PBB) has gained prominence worldwide. The present study addresses the challenges of implementing and managing PBB in the Russian public sector, with a particular focus on the Orel region’s long-term targeted healthcare programs. Drawing on case study analysis and empirical evidence, the study identifies specific challenges hindering effective PBB implementation, including effectiveness issues, revenue generation concerns, and passive actors with limited knowledge and skills. The study sheds light on the complexities and tensions arising from a top-down approach to PBB implementation and offers insights into prioritizing expenditures amid economic and geopolitical factors in emerging market economies like Russia.